Ameliorative effect of apple pomace and mango peels against hyperlipidemia and lipid peroxidation induced by hyperlipidemic diet - Umbreen, Huma; Arshad, Muhammad Umair; Noreen, Razia; Aftab, Kiran (Penerbit Universiti Kebangsaan Malaysia, 2020)
Diet induced hyperlipidemia is a major cause for atherosclerosis, lipid peroxidation, and fatty liver diseases. Fruit processing waste rich in dietary fiber and antioxidant capacity can be an economical way to manage such risk factors. The major objective of the present study was to manage hyperlipidemia by including apple pomace and mango peels in daily diet. Dry powder obtained from apple pomace, mango peels and their mixture was added to the normal chow on replacement basis by 12%. These were fed to the rats along with hyperlipidemic diet to the experimental groups (N=30, 10/group), while control group (N=10) was fed hyperlipidemic diet alone. The rats were analyzed for water and feed intake, body weight, organs to body weight ratio, glucose concentration, lipid profile, lipid peroxidation test, liver cholesterol, and liver and renal function tests. The results showed that high cholesterol in diet was well managed by rat groups on apple pomace and mango peels supplement. The mango peels powder was found to be more effective as compared to apple pomace powder against hyperlipidemia. Mango peels and apple pomace powders not only improved the lipid profile but also resulted in lower liver cholesterol concentration and better lipid peroxidation status of the experimental rats as compared to control group. It can be concluded that fruit processing waste specially mango peels can be cost effective tool to manage diet induced hyperlipidemia, lipid peroxidation and fatty liver diseases.